A new species of Arctoseius Thor, 1930 (Acari: Ascidae) from taiga regions of the Palaearctic, with a key to Arctoseius species of Fennoscandia, NW Europe - Makarova, Olga L.; Huhta, Veikko (Zootaxa, 2017)
A new mesostigmatid mite species belonging to the genus Arctoseius Thor, 1930, is described based on material from subarctic coniferous forests, Finland, and Altai highlands, Russia. Arctoseius ambiguus sp. nov. is similar to Arctoseius venustulus (Berlese, 1916), but can be distinguished from the latter by its larger size, wider dorsal shield, weakly sclerotized presternal platelets, pronounced differences in the length of opisthonotal setae, and distinct punctation of the anal shield. A key for 15 Arctoseius species recorded in continental North-Western Europe (Fennoscandia) is given. The Fennoscandian fauna of Arctoseius species is rather specialised. It includes four European temperate species and five cryobiontic (arctic, arcto-montane, arcto-boreo-montane) ones.